SUBTRACTION MADE EASY FOR PUPILS WITH LEARNING DIFFICULTIES (Proceedings of International Conference on Special Education, 2015)
Subtraction is the foundational concept in Mathematics. Unfortunately, pupils with learning difficulties often find it challenging as it entails counting backward. Going gets tough for these pupils when the number gets bigger and involves regrouping. These phenomena were observed among five pupils in a second grade remedial class in a suburban primary school. From the error analysis and the subsequent individual interviews, these pupils showed a lack of understanding of the place value and subtraction concept although they generally grasped the concept of one to one correspondence. In addition they were found to have retention difficulty and thus lost interest and patience in learning mathematical skills. Therefore, this action research was conducted to improve the subtraction skills for these five pupils as research participants. The focused skill was subtraction with regrouping within 100. For this purpose, a unique subtraction board was devised based on Bruner’s ConcretePictorial-Abstract (CPA) concept. In the first phase, participants revisited the concept of place value using a story. Next, tangible objects were used for concrete concept formation followed by drawing and finally abstract numbers in a progressive manner depending on participants’ pace and progress. A catchy song was created to enhance skill retention. Besides, drills and practice were made more fun in the form of computer games devised by the authors. The intervention was conducted 5 days a week, 1 hour per day for 2 weeks. Pretest and posttest results showed significant improvement after the intervention. Findings from ensuing interviews and observations demonstrated that repeated use of manipulatives helped participants visualize subtraction of objects and gave them clearer picture on place value. The findings indicated that scaffolds of manipulatives and drawings which were slowly removed could help participants in understanding abstract mathematics concept while the song and computer games served as memory enhancer and intriguing drills.